Uma análise do conceito de desenvolvimento sustentável através da comparação de agendas internacionais: Objetivos de Desenvolvimento Sustentável (ODS) e a Iniciativa Cidades Emergentes e Sustentáveis (ICES) - Oliveira, Ingra Freire de (2019)
The purpose of this study is to compare the sustainable development conceptions of the United Nations Sustainable Development Goals agendas and the Inter-American Development Bank's Emerging and Sustainable Cities Initiative by comparing their indicators. The choice of indicators for the analysis was based on the fundamental role played by this tool in the translation of the concepts adopted in theory by the agendas, objectively defining the actual commitments to be made by the cities / countries. To make it possible to compare the two ESCI and SDGs development agendas, a literary review was carried out on the two key points of the paper: the concept of sustainable development and the importance of indicators for measuring social phenomena. Linked to these two points, we present the concepts adopted by the agendas, and explain the process of construction of the indicators used by each of them. For the indicator tables, a comparison standard was established that made possible the more detailed study of each one of them, helping to identify the common and divergent points presented by ICES and the SDGs and also in the analysis of their contents individually. As a result of the analysis, despite having the same object and departing from a similar conception of the understanding of sustainable development, the agendas presented a low convergence between their contents. In addition, it was observed that both agendas, in general, comply with their preliminary concept of SD proposed by presenting indicators compatible with their purposes.